BioHelm smart hockey helmet: a conceptual wearable system for protecting and empowering female athletes - Parrucci, A. (Rochester Institute of Technology, 2022)
Women`s ice hockey is one of the fastest growing sports in the world and needs the most articles of protective equipment. At the National Collegiate Athletic Association (NCAA) level, not only do these athletes need to adapt to team issued equipment that rarely fits comfortably or safely but must also consider the important facets that impact overall performance. The main objective of this project is to promote inclusivity while protecting, empowering and educating athletes in an ethical, noninvasive manner to positively impact the culture of women`s sports. Overexertion at the NCAA level increases exponentially due to the intense training and competition schedules and living the full-time "college lifestyle." This lifestyle can have negative anatomical, physiological, and psychological impacts on the athletes. The year-long design project studied multiple perspectives, including players, coaches, trainers and doctors, using applied "design thinking" to create a holistic approach to solving sports equipment issues for women. This proposed system could improve the physical, physiological and emotional wellbeing of the athletes. The system combines physical biomarkers with player input in a multi-layered, systematic approach and to consider the potential of AI and "big data" gathered from the wearable technology athletic equipment to design the future for elite women`s sports.